Zirconia nano-colloids transfer from continuous hydrothermal synthesis to inkjet printing. Issue 1 (January 2019) - Rosa, M.; Gooden, P.N.; Butterworth, S.; Zielke, P.; Kiebach, R.; Xu, Y.; Gadea, C.; Esposito, V.
Abstract: Water dispersions of nanometric yttria stabilized zirconia (YSZ) particles synthesized by Continuous Hydrothermal Synthesis are transferred into nano-inks for thin film deposition. YSZ nanoparticles are synthesized in supercritical conditions resulting in highly dispersed crystals of 10 nm in size. The rheology of the colloid is tailored to achieve inkjet printability (Z) by using additives for regulating viscosity and surface tension. Inks with a wide range of properties are produced. A remarkable effect of nanoparticles on the ink printability is registered even at solid load < 1%vol. In particular, nanoparticles hinder the droplet formation at low values of the printability while suitable jetting is observed at high Z values, i.e. Z ≈ 20. For the optimized inks, we achieve high quality printing with lateral and thickness resolutions of 70 μm and ca. 250 nm respectively, as well as self-levelling effect with a reduction of the substrate roughness. Densification is achieved at sintering temperatures below 1200 °C.